Arctic National Wildlife Refuge : Bibliography-in-Brief. (U.S. Congressional Research., 1988)
Presents an annotated bibliography on proposed oil and gas development in the Arctic National Wildlife Refuge, and on the environmental impact of the oil industry in Alaska.